Normative Data of Thyroid Volume-Ultrasonographic Evaluation of 422 Subjects Aged 0-55 Years - (:unkn) unknown (My University, 2015)
0

Objective: To establish local normative data of thyroid volume assessed by ultrasonography in subjects aged 0-55 years living in İstanbul, Turkey.Methods: Subjects without any known history of thyroid disease, of major surgery and/or chronic disease were enrolled in the study and evaluated by physical examination and thyroid ultrasonography. Thyroid gland and isthmus at usual location, each lateral lobe volume with three dimensions, ectopic thyroid tissue and echogenicity of the gland were assessed.Results: Initially, 494 subjects were enrolled in the study. Subjects showing heterogeneous thyroid parenchyma (n=21) and/or nodule (n=51) in ultrasonography were excluded. Final analysis covered 422 subjects (216 males, 206 females). Thyroid volume was found to significantly correlate with height, weight, age and body surface area (r=0.661, r=0.712, r=0.772 and r=0.779, respectively; p<0.0001 for all). These correlations were even stronger in subjects younger than 18 years (r=0.758, r=0.800, r=0.815 and r=0.802, respectively; p<0.0001 for all).Conclusion: The study provides updated reference norms for thyroid volume in Turkish subjects which can be used in the diagnosis and follow-up of patients with thyroid diseases.
Keywords: Endokrinoloji ve Metabolizma; Pediatri